INVESTMENT PROJECTS FINANCING THROUGH LOANS OF COMMERCIAL BANKS (World Economics and Finance Bulletin, 2024)
This article depicts the various sources of funding for investment projects, along with defining what an investment project is and outlining its characteristics, processes, and different forms of bank financing. It also details the primary goals of financing and the evaluation methods for investment projects. Additionally, it presents the ultimate outcomes that lenders aim to achieve.
Keywords: credit; investment project; investment loan